Developing Literacy and Numeracy-Based Mathematical Reasoning Question Items for High School Students - Feriyanto Feriyanto; Deka Anjariyah; Taswirul Afkar (Universitas Negeri Yogyakarta, 2023)
This study aims to describe the process and the result of developing literacy and numeracy-based mathematical reasoning questions for high school students in Mojokerto that are valid, practical, and effective. The subjects of this study are 12th-grade students at the public senior high school of Gondang. The research instruments are observation sheets, interview guidelines, response questionnaires, and mathematical reasoning ability tests. At the same time, the data analysis in this study is qualitative and quantitative. The result of this research is (1) In The preliminary stage, students' mathematical reasoning abilities still needed to improve with evidence of difficulties in identifying and relating the information provided to conclusions. The researchers and teachers determine the research subjects and research time. In the formative evaluation stage, for self-evaluation, the researcher analyzed the material and curriculum. The third stage is prototyping, consisting of expert review, one-to-one, small group, and field tests. In the expert review, prototype II was produced, which was very valid, with an overall average of 4.24. Three students were tested in the one-to-one, and three prototypes were built. A trial was conducted in the small group, and a prototype IV was produced. The field test, testing, and production of mathematical modules met the valid, practical, and effective criteria. (2) The study's findings include numeracy and literacy-based mathematical reasoning problems that satisfy the validity criteria with proper categories and the practical requirements with extremely positive standards, in addition to achieving the efficacy criterion of the questions through students' mathematical reasoning.